Strategic Thinking and Its Impact on Organizational Compatibility: An Analytical Study In The Iraqi Media Network - Naeem Hamish, Fatima; Mohsen Salman, Saadoun (Journal of Economics and Administrative Sciences, 2024)
Purpose: This research aims to achieve the most critical objective: to reveal the relationship between strategic thinking and organizational compatibility in the Iraqi Media Network. Theoretical Framework: In light of what researchers (Srivastava, S., & D’Souza, 2021) and (Nafei, 2017)have stated, this study provides practical guidelines for improving strategic thinking in the face of challenges and difficulties to enhance organizational compatibility. Design/Methodology/Approach: The study aimed to analyze the data of employees in the Iraqi Media Network (2024) using strategic thinking and its dimensions (organizational thinking, processing divergent ideas, contemplation) on the impact of organizational compatibility and its dimensions (organizational loyalty, organizational similarity, organizational membership or affiliation). Research Implications: The results confirm the existence of a statistically significant relationship between strategic thinking and organizational compatibility. Originality/Value: This study seeks to bridge the knowledge gap by analyzing and identifying the essential skills and qualities that contribute to developing strategic thinking, enhancing organizational alignment, and applying these skills in different work environments to achieve better organizational performance.